«Пушторг» как ключевое произведение русского конструктивизма - Шакарян, Константин (Вестник Ереванского Университета: Русская Филология, 2023)
The article is an attempt to study the poetics and ideology of the literary grouping of the 1920s LCC (Literary Center of Constructivists) based on the work of its leader Ilya Selvinsky, in particular, his novel in verse «Pushtorg».LCC was organized in 1923, becoming in the second half of the 1920s one of the most famous and influential literary groups in the USSR. In 1930, he shared the fate of other groups and trends that announced their self-dissolution under pressure from the Central Committee of the party.The novel in verse «Pushtorg» was written by I. Selvinsky in 1927, in 1928 it was published with abbreviations in the magazine «Krasnaya Nov», the full text was published in a separate edition in 1929 (reprinted in 1931).The novel had a great resonance, as evidenced by dozens of reviews and mentions in the press of 1928-1930.In «Pushtorg» Selvinsky raised burning issues of modernity, the main of which was the problem of the intelligentsia and revolution – one of the key problems in the poetry of constructivism. Selvinsky's solution to this problem could not satisfy party criticism – as a result, the overwhelming majority of responses to the novel were sharply negative.In the first part of this article, the features of the poetics of constructivism are investigated on the basis of the theoretical works of K. Zelinsky and I. Selvinsky, their embodiment in the novel "Pushtorg" is traced.The second part examines the historical context in which "Pushtorg" and other works of Selvinsky were created, links are established between verses from Selvinsky's first book "Records" (1926) and "Pushtorg" – and the phenomena of social and literary life of the 1910s-20s.Attention is also paid to the interpretations of «Pushtorg» by soviet and modern researchers.
Keywords: И. Сельвинский; ЛЦК; русский конструктивизм; роман в стихах; 1920-е годы